Investigating the predictive effect of neutrophil to lymphocyte ratio as an inflammatory marker in the spontaneous excretion of ureteral stones - Deldadeh-Moghaddam, Hamid; Cheraghi-Digaleh, Tina (International Journal of Research in Medical Sciences, 2023)
Background: The size and location of the stone have been suggested as the most important predictors of the possibility of spontaneous passage of the stone. The aim of this study was to investigate the predictive effect of neutrophil to lymphocyte ratio as an inflammatory marker in the spontaneous excretion of ureteral stones. Methods: This descriptive-analytical study was done on 95 patients with ureteral stone during 2020-21. Required data include sex, age, BMI, previous history of stone, previous history of spontaneous passage of stone, side, location and size of stones, spontaneous passage of stone, and neutrophil and lymphocyte ratio were extracted from file of patients. The presence of the stone and its characteristics were confirmed by ultrasound. Patients were followed up for 2 weeks to determine whether or not the stone passed spontaneously. Results: There was a significant relationship between spontaneous passage of ureteral stone with stone size, location, and neutrophil to lymphocyte ratio. The cut-off points of neutrophil to lymphocyte ratio for predicting spontaneous passage of ureteral stone was 2.52, so that patients with higher values were faced with a 4.2-fold increase in the risk of no spontaneous passage of stones (OR=4.202, 95% CI: 1.563-11.298, Sig.=0.004). Conclusions: The results of the study showed that the ratio of neutrophils to lymphocytes is a significant predictor of spontaneous passage of ureteral stones, so that if used in addition to the size and location of the stone, the accuracy of predicting patients who benefit from conservative management, increase significantly.